ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF USAHATANI UBI KAYU DI KECAMATAN BLAMBANGAN PAGAR KABUPATEN LAMPUNG UTARA - Sayu Hadiyati Iswara; Raden Hanung Ismono; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze the comparative and competitive advantages of two varieties of cassava, and determine the sensitivity due to changes in output prices, production volumes, and input prices to the comparative and competitive advantages of cassava farming in Blambangan Pagar Sub-district of North Lampung Regency.  This research is a survey research involving 50 cassava farmers who were selected intentionally consisting of 25 farmers of Cassesart varieties and 25 farmers of Thailand varieties.  To answer these objectives, the study uses PAM analysis (Policy Analysis Matrix).  The results showed that Cassesart variety (UJ-5) cassava farming had a DRCR value of 0,15 and PCR of 0,46 so it was more competitive than Thailand variety (UJ-3) cassava farming which had a DRCR value 0f 0,18 and PCR of 0,57.  If there is a decrease in the output price for Cassesart variety (UJ-5) cassava by 4,93% and Thailand variety (UJ-3) cassava by 5,32%, a decrease in production volume is 4,70%, and an increase in input prices (Urea fertilizer 21,32%, SP-36 fertilizer 34,40%, and NPK Phonska fertilizer 54,01%) due to the removal of fertilizer subsidies by the government, cassava farming is insensitive, therefore, despite changes in output prices, production volume, and the price of these inputs, cassava farming still has a competitive edge.   Keywords : cassava, comparative, competitive, PAM